Comparative metabolomic analyses of Dendrobium officinale Kimura et Migo responding to UV-B radiation reveal variations in the metabolisms associated with its bioactive ingredients - Yue Chen; Qi Shen; Ping Lv; Chongbo Sun (PeerJ, 2020)
Background Dendrobium officinale Kimura et Migo, a member of the genus Dendrobium, is a traditional Chinese medicine with high commercial value. The positive roles of UV-B radiation on active ingredient metabolism in various medicinal plants have been studied. However, the metabolic responses of D. officinale stems to UV-B treatment is largely unknown. Methods An untargeted metabolomics method was used to investigate the metabolic variations in D. officinale stems between the control and UV-B treatments. Results In total, 3,655 annotated metabolites, including 640 up- and 783 down-regulated metabolites, were identified and grouped into various primary metabolic categories. Then, a number of metabolites involved in the polysaccharide, alkaloid and flavonoid biosynthesis pathways were identified. For polysaccharide biosynthesis, several intermediate products, such as pyruvate, secologanate, tryptophan and secologanin, were significantly up-regulated by the UV-B treatment. For polysaccharide biosynthesis, many key fundamental building blocks, from the glycolysis, starch and sucrose metabolism, and fructose and mannose metabolism pathways, were induced by the UV-B treatment. For flavonoid metabolism, accumulations of several intermediate products of chalcone synthase, chalcone isomerase and flavanone 3-hydroxylase were affected by the UV-B treatment, indicating an involvement of UV-B in flavonoid biosynthesis. The UV-B induced accumulation of polysaccharides, alkaloids and flavonoids was confirmed by HPLC analysis. Our study will help to understand the effects of UV-B on the accumulation of active ingredients in D. officinale.